Impact of Instructional Intervention about Personal Hygiene upon Women who complain Pelvic Inflammatory Disease - Fakhry, faeza; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2016)
Objective: To determine the impact of personal hygiene on woman who complain pelvic inflammatory disease Methodology: A quasi experimental study in the High Institute Infertility Diagnostic and A.R.T.(assistance reproductive technology) in AL-Kadimya city and al-Emamian al Kadmain medical city hospital. The sample collected during (26th ) January – (30th ) April 2014. A purposive sample of (60) women, (30) of them regard as study group and (30) regard as a control group whom they take routine care in the institute and hospital. The questionnaire consisted of socio-demographic data, reproductive health for women, information related to pelvic inflammatory disease, and information related to personal hygiene. pilot study has been carried out to test the reliability of the questionnaire and content validity has been carried out through the (15)experts. Descriptive and inferential statistical analyses are used to analyze the data . Results : The results presented that woman who used special chemical disinfectant solutions and irrigations for clean the perineal area (66.7%) for both samples, who are using herbal soap (53%) (36.7%) for the study and control sample respectively, washing the area daily as range from (1-2) times were (46.7%) (43.3%) for the study and control sample, washing the area from front to back (80%) (63.3%) for the study and control sample, who leave the area dry (50%) (56.7%) for the study and control sample, who used healthy tissues for drying the area (50%) (60%0 for the study and control sample, with her change underwear daily (100%) (90%) for the study and control sample, with her expose underwear to the sun shine (76.7%) (70.7%) for the study and control sample, with wear cotton cloths (60%) (50%) for the study and control sample, with change the sanitary pads in the menstrual period during the day as the range from (1-2) times (60%) (70%) for the study and control sample . Recommendations: Setting up procedures of instructional and educational programs to the women who suffering of pelvic inflammatory disease, by using healthy methods of personal hygiene (perennial’s care area), and during intercourse, such as using condom or external ejaculation by the husband, or abstinence sexual intercourse during treatment course in case taking the treatment both of partners